Comparison of Concrete and Steel Jacket Methods for Reinforcing A Concrete Bridge Pier by Numerical and Experimental Studies - Faghihmaleki, Hadi (Makara Journal of Technology, 2021)
Various rehabilitation and strengthening procedures have been developed in recent decades. A study to determine which methods can be implemented to increase the useful life of the bridge before strengthening must be performed. In this study, the seismic behavior of a reinforced concrete bridge pier with dimension 3.5 × 3.5 m, which was reinforced by two steel and a concrete jacket, was investigated. Nonlinear geometric models and materials were analyzed to estimate the seismic parameters of the pier. Results show an increase in energy absorption, ultimate strength, and ductility for the steel jacket, as well as a greater increase in the concrete jacket. Using a box concrete jacket with a dimension of 3.5 × 3.5 m, the increase in percentages of energy absorption, ultimate strength, and ductility were 38, 14, and 13, respectively. Therefore, the concrete jacket enhances the mentioned parameters.